DOES SNATCHING FREQUENCY REALLY INDICATE FOOD INGESTION IN THE NILE TILAPIA - Carrieri, M. P.; Volpato, G. L. (Elsevier B.V., 1991)
The fitness of the snatching frequency as an indicator of food intake in Nile tilapia finger-lings, Oreochromis niloticus (L), was studied. Five groups of four individuals each were used after a two-day starvation period. The hierarchical rank among individuals in the same group was registered. Food in the form of tiny pellets (ranging from 1.30 to 1.95 mm in diameter) was offered, and the individual snatching frequency was observed during a 20-min period. The animals were then sacrificed for evaluation of stomach contents. It was concluded that snatching frequency is not a good parameter to indicate individual food intake in this species when fed as a group with pellets crushed into tiny particles. This raises a problem for investigations that require evaluation of the cumulative effect of competition on food intake, such as growth or conversion efficiency studies. Furthermore, a very low correlation between snatching frequency and food intake was shown in the third hierarchical rank. It is suggested that the linearity assumed in such hierarchies should be reconsidered.
Keywords: NILE TILAPIA; OREOCHROMIS-NILOTICUS; HETEROGENEOUS GROWTH; SOCIAL HIERARCHY; FOOD COMPETITION; SNATCHING FREQUENCY; INGESTED FOOD